Peran Guru PAI dalam Membentuk Kesadaran Hukum Berlalu Lintas Pada Siswa Kelas XII di SMK Texmaco Purwasari - Alif Kurniawan; Surya Hadi Darma; Abdurrahman Saleh (Paedagogie: Jurnal Pendidikan dan studi Islam, 2021)
This research is based on the results of observations made by the author, namely the number of victims of traffic accidents aged 16-30 years, many victims of traffic accidents, traffic accidents in Karawang every year lose up to 500 children's lives under the age of 25 years, and including six students from class XII SMK Texmaco Purwasari among them. The author assumes that the incident was caused by the low awareness of students in understanding traffic laws. This study aimed to find out the answers to assumptions regarding students' awareness in understanding traffic laws and the role of teachers in shaping traffic awareness, especially at SMK TEXMACO Purwasari. The approach used by the researcher is a descriptive qualitative approach with theoretical analysis of -O-R (Stimulus Organism Response) to identify that student awareness can be formed through the communication of the role of the PAI teacher. This study indicates that the role of the PAI teacher in shaping student traffic law awareness includes: a) the first as an Informator, b) the dual role as an organizer, c) the third role as a motivator. d) The fourth role is as a facilitator, e) the fifth role is as a supervisor, f) the last role is as a class manager.